Studies of Islam, Economics, and Governance: A Survey of Some New Developments (American Journal of Islam and Society, 1994)
IntroductionThis paper is a report on the state of research in two areas of Islamicstudies: Islam and economics and Islam and governance. I researched andwrote it as part of my internship at the Ford Foundation during the summerof 1992. On Discourse. The study of Islam in the United States has moved far beyondthe traditional historical and philological methods. This is perhapsbest explained by the development of analytically rigorous social sciencemethods that have contributed to a better balance between the humanisticconcerns of the more traditional approaches and efforts at systematizingthe study of Islam and classifying it across boundaries of communities,religions, even epochs. This is said to have s t a d with the developmentof irenic attitudes towards Islam, which changed the direction of westemorientalist writings from indifference (at best) and often open hostility toand contempt of Islamic values (however they were understood) to phenomenologicalworks by scholars who saw the study of Islam as somethingto be taken seriously and for its own sake, which is best exemplifiedby Clifford Geertz's Islam Observed.The work of Edward Said contested this evolution, and the publicationof his Orientalism has been described as "a stick of dynamite"' that,despite its impact in mobilizing a reevaluation of the field, was unwarrantedin its pessimism. In any case, the field has continued to evolve,with the most powerful force moving it being the subject itself. Thephenomenological/orientalist approach, if we can point to one today, ...